Invisible women true stories of courage and survival - Trevane, Jacky (London Hodder & Stoughton, 2005)
In Fatwa Jacky Trevane told her nightmare story of domestic abuse and her escape from the husband she had married in Cairo after a whirlwind holiday romance. Having finally escaped with her two daughters, Jacky now lives in hiding with a fatwa hanging over her, in fear of her own and her daughters' safety.
UCWS-3292g donated by Adrienne Maguddayao - May 2018
Keywords: Abused women -- Personal narratives